Testing Of Consistent Trends in Stock Performance In The Nairobi Securities Exchange - Ndegwa, James N.; Kiweu, Joséphat M. (Department of Business Administration, School of Business, University of Nairobi., 2015)
Consistent stock performance contradicts random adjustment of stock prices in efficient markets and is thus anomalous despite the potential of generating significant profits for investors. This research set out to test the existence of consistent stock performance in the NSE during the years 2001 to 2010 and to examine whether consistent stock performance is associated with efficiency of NSE. Balanced monthly closing average stock price data was employed for 32 sample stocks drawn using purposive sampling technique from a population of 56 stocks listed in the NSE during the study period. In order to identify consistent stock performance, frequency tests were employed. In order to test association between consistent stock performance and efficiency of NSE 3 tests were employed including: t-test to test the significance of abnormal returns of consistent stock performance. Runs serial correlation test was employed to test serial correlation of stock returns. Spearman rank correlation was also employed to test volatility of stock prices with time. The results indicated weak presence of consistent stock performance in the NSE and that abnormal returns of consistently performing stocks were insignificant. There was also zero serial correlation of stock returns and stock prices of consistently performing stocks exhibited low volatility with time. The overall results indicate that NSE may be weak form efficient. This research contributes to new knowledge by combining the alternative definitions of consistent stock performance to minimize on the inherent weaknesses of each definition(cross sectional and longitudinal) which have in the past been studied independently.
Keywords: Consistent stock performance; Serial correlation; Volatility